Surgical Management of Cranial Cervical Esophageal Diverticulum in a Buffalo - Rafee, Malik Abu; Bhat, Abas Rashid; Pawde, Abhjit (Journal of Buffalo Science, 2015)
A 3 year old female buffalo calf was presented, with the history of anorexia, dysphagia, regurgitation, frothy salivation. On physical examination a soft bulge was observed. Esophagotomy was performed and the contents removed. The contents lodged at the site of diverticulum were mainly the regurgitated ruminal mass. The edges were trimmed with scissors and mucosal layer sutured using 1/0 vicryl. The muscular wall sutured using 10 Vicryl by simple continuous suture pattern. The skin incision was closed in routine manner. The animal recovered without any complication.